What Determines the Choice Between Sukuk vs Bonds? - Ryan Kusuma Wardhana; Rahmat Heru (Economics, Business, Accounting & Society Review, 2022)
Funding for investments that can be obtained from various alternative sources of financing. However, the ideal funding desired by the investment manager is the most profitable funding and in line with the company's goals. Conventional bonds have long been a popular choice of management, while Islamic bonds tend not to be well recognized by management. In that, Islamic bonds have various advantages that can provide benefits to management.  This study aims to investigate factors that determine public listed corporations in 3-ASEAN nations' decisions to issue corporate bonds or sukuk. For a sample of 124 sukuk and bonds issued between 2012 and 2017, we examine the influence of free cash flow as a proxy for agency cost, growth, and leverage on the decision between bond and sukuk issuance. According to the findings of binary logistic regression, firms with high free cash flow and leverage choose sukuk over conventional bonds. Firms with stronger growth, on the other hand, choose conventional bonds over sukuk. Our findings are consistent with the agency's cost-cutting strategy for free cash flow. The research has the implication that conventional bonds are preferred by fast growing companies.